PENGARUH KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIORS (OCB) PADA CV. MULIA ABADI - Herman; Armansyah, Armansyah (Program Studi Manajemen Keuangan Syariah, 2025)
The purpose of this study was to determine the effect of Job Satisfaction on Organizational Citizenship Behavior (OCB) at CV. Mulia Abadi. The method used in this study is a quantitative method. The population in this study were 35 employees and were also used as samples, with a sample technique of saturated samples. The method in this study is quantitative. Based on the results of the research conducted, the following conclusions can be drawn: Job satisfaction has a good effect on Organizational Citizenship Behavior. This means that employee satisfaction as seen from satisfaction with opportunities for promotion, satisfaction with organizational policies, satisfaction with superior performance, satisfaction with the work environment, satisfaction with communication within the organization can have an effect on Organizational Citizenship Behavior. Employee satisfaction partially affects Organizational Citizenship Behavior. This means that employee satisfaction can have an effect on Organizational Citizenship Behavior.